POLA INTEROGATIF PENYIDIK PADA SAKSI AHLI BAHASA PADA KASUS DELIK ADUAN - Ika Arifianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
Legal language can develop in accordance with the confession of the suspect in the Interrogation Report process. The Interrogation Report is a state secret that should not be published to the general public. However, in the interest of this research, the Interrogation Report process is allowed only to the certain extent. The novelty of this research is in the field of data collection which focus on the interrogation of investigators with legal language experts. This study is normative legal research which use normative legal approach and consists of studying legal principles. The data in this study are from police interrogation report 2013 on complaints offence about domestic violence committed by members of the Indonesian police.After analyzing the interrogation result, The results of this research show first, the structure of the discourse of  Interrogation report in the complaint offense case at the Central Java Regional Police with the in the following form: opening section, content section, and closing section, which clarify the structure of the content related to the identity of expert witnesses according to scientific expertise, statements of truthful reporting related to the legal realm, clarity based on information and evidence. Second, qualified investigators are needed. This research can give new contribution in the world of linguistics and police research and a reference for further research in the field of pragmatics, critical pragmatics and  can also be followed up in the field of forensic linguistics. The study of pragmatics and forensic linguistics is a field of applied linguistics that deserves to be researched in the context of efforts to develop linguistic scholarship. This research data can be developed for forensic linguistic research. Forensic linguistics is a new field of science in the field of applied linguistics.